Parenting practices in Kerala: A cross-sectional study' - Nair, M. K. C., Sumaraj, L., Padmamohan, L., Radhakrishnan, R., Nair, V. Rajasenan, George, B. and Kumar, G.Suresh (Vulnerable Children and Youth Studies,2:1,71 - 79, 2007)
This paper presents outcomes of a cross-sectional study conducted in Kerala, India on the parenting practices of 0-3-year-old children supported by UNICEF. The aim of the study was to explore early child-care practices from conception to 3 years with a focus on the family as caregiver. Positive attitudes were observed in key indicators of child-rearing practices among the study population. No major difference was observed among women of various sociodemographic backgrounds in this respect. Early child-care practices are reaching high standards, even in tribal and economically backward areas. This may be an indicator of the overall achievement of Kerala in general health status. Even though parenting practices are generally healthy, as revealed through focus-group discussions, parents face many problems in child rearing and would benefit from training in parenting practices.